Comparative Analysis of Teacher Performance in the Teaching and Learning Process - Aminah Rehalat (IJECA (International Journal of Education and Curriculum Application), 2021)
This study aims to determine the comparison of teacher performance in the teaching and learning process. Teacher performance is seen from three indicators, namely the stage of planning learning activities, the stage of implementing learning activities and the evaluation / assessment stage of learning. This type of research is a qualitative descriptive approach using observation data collection techniques, interviews, and documentation and the subject of this research is the social studies subject teacher at SMP Negeri A and MTS B. The results showed that the performance of teachers in the teaching and learning process (case studies of social studies subject teachers at SMP Negeri A and Mts B was in a good category for Mts B and good enough for SMP Negeri A which can be seen from the stage planning learning activities and the evaluation / assessment stage of learning. At the planning stage, social studies teacher learning activities do not experience obstacles and have been implemented properly according to the first indicator where the social studies teacher already has the ability to arrange learning tool activities (called RPP).